The usage of polidocanol in varicose disease treatment - Valeriu Ardeleanu; Lavinia-Alexandra Moroianu; Cecilia Curis; Alin Laurentiu Tatu; Iasmina- Raisa Ardeleanu (Journal of Mind and Medical Sciences, 2024)
Chronic varicose veins disease is widespread worldwide (up to 60% in the adult population), with a significant impact on patients' quality of life and a high cost to society, both due to treatment and the limitation of physical activity imposed by the disease. This article presents a retrospective study on a number of 14 patients treated in Arestetic Clinic in Galati, for a period of one year. The patients included in the study presented reticular and varicose veins up to 6 mm in diameter and under 14 mm on the saphenous vein. Patients completed the Aberdeen Varicose Disease Questionnaire (excluding the first part of the questionnaire) and the Venous Clinical Severity Score was used by the physician. Doppler ultrasound was used for preoperative evaluation and postoperative monitoring. Polidocanol was administered in concentrations of 0.5% and 2%, with the patients being monitored one year after treatment. All patients were declared satisfied with the results and 1 year after treatment no recurrences were found. Polidocanol sclerotherapy is a safe, easy-to-administer, low-cost treatment with no healing time and can be administered multiple times if needed, with minimal risks of complications. Aesthetic results are good, with an important symptom remission rate and high patient satisfaction. Complications were rare and minor (represented by local hyperpigmentation and hardening of the injected path), and the recurrence rate is comparable to surgical treatment.